2022
DOI: 10.1302/0301-620x.104b1.bjj-2021-0761.r1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of soft-tissue sarcoma in nonagenarians

Abstract: Aims Current literature suggests that survival outcomes and local recurrence rates of primary soft-tissue sarcoma diagnosed in the very elderly age range, (over 90 years), are comparable with those in patients diagnosed under the age of 75 years. Our aim is to quantify these outcomes with a view to rationalizing management and follow-up for very elderly patients. Methods Retrospective access to our prospectively maintained oncology database yielded a cohort of 48 patients across 23 years with a median follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…168 In a retrospective database review, the impact of age showed an overall lower local recurrence rate in primary amputations of elderly patients (over 90 years) when compared to limb salvage. 169 Patient-reported outcomes are another important aspect of clinical considerations, as they often guide a multidisciplinary approach to improving physical function 170 and quality of life through functional rehabilitation. 171 Importantly, a discussion on the importance of awareness and education among healthcare providers, as postulated in a review, 172 is a necessary step to improving the multidisciplinary approach of cancer care, including early and accurate referral to specialized sarcoma centers, critical for improving patient outcomes.…”
Section: Clinical Treatment Patterns and Outcomesmentioning
confidence: 99%
“…168 In a retrospective database review, the impact of age showed an overall lower local recurrence rate in primary amputations of elderly patients (over 90 years) when compared to limb salvage. 169 Patient-reported outcomes are another important aspect of clinical considerations, as they often guide a multidisciplinary approach to improving physical function 170 and quality of life through functional rehabilitation. 171 Importantly, a discussion on the importance of awareness and education among healthcare providers, as postulated in a review, 172 is a necessary step to improving the multidisciplinary approach of cancer care, including early and accurate referral to specialized sarcoma centers, critical for improving patient outcomes.…”
Section: Clinical Treatment Patterns and Outcomesmentioning
confidence: 99%
“…Table II shows a number of recent studies on soft-tissue tumors [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] .…”
Section: Soft-tissue Tumorsmentioning
confidence: 99%
“…Hartley 47 In this large database study, the authors used propensity score matching to compare outcomes between patients with a softtissue sarcoma of the extremity who had an unplanned excision followed by a re-excision and patients who only had a primary planned excision, and found that there was no difference in mortality or local failure. The authors reviewed the outcomes of 1,775 patients with sarcoma referred to a large national referral center before and after the issuance of the NICE guidelines in the United Kingdom in 2006.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations